2018
DOI: 10.1162/jocn_a_01311
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Correlates of Relational Reasoning: A Meta-analysis of 47 Functional Magnetic Resonance Studies

Abstract: It is a core cognitive ability of humans to represent and reason about relational information, such as "the train station is north of the hotel" or "Charles is richer than Jim." However, the neural processes underlying the ability to draw conclusions about relations are still not sufficiently understood. Central open questions are as follows: (1) What are the neural correlates of relational reasoning? (2) Where can deductive and inductive reasoning be localized? (3) What is the impact of different informationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 93 publications
3
23
0
Order By: Relevance
“…This is consistent with several previous neuroimaging studies that have also found that transitive reasoning mainly relies on regions in and around the IPS (Goel and Dolan 2001, Acuna, Eliassen et al 2002, Knauff, Mulack et al 2002, Knauff, Fangmeier et al 2003, Heckers, Zalesak et al 2004, Fangmeier, Knauff et al 2006, Hinton, Dymond et al 2010, Prado, Mutreja et al 2013. For example, quantitative meta-analyses of the literature show that transitive reasoning consistently activates the left and right IPS across studies in adults (Prado, Chadha et al 2011, Wertheim andRagni 2018). A recent study in children also points to the involvement of the parietal cortex in transitive reasoning (Mathieu, Booth et al 2015).…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with several previous neuroimaging studies that have also found that transitive reasoning mainly relies on regions in and around the IPS (Goel and Dolan 2001, Acuna, Eliassen et al 2002, Knauff, Mulack et al 2002, Knauff, Fangmeier et al 2003, Heckers, Zalesak et al 2004, Fangmeier, Knauff et al 2006, Hinton, Dymond et al 2010, Prado, Mutreja et al 2013. For example, quantitative meta-analyses of the literature show that transitive reasoning consistently activates the left and right IPS across studies in adults (Prado, Chadha et al 2011, Wertheim andRagni 2018). A recent study in children also points to the involvement of the parietal cortex in transitive reasoning (Mathieu, Booth et al 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Other forms documented in the literature are unaddressed. Also, the brain activities of individuals solving select Raven's items are typically registered by neuroimaging techniques (e.g., Dumontheil et al, 2010;Wertheim and Ragni, 2018;Gray and Holyoak, 2020). The expertise, funds, and facilities that these neuroimaging techniques require render them impractical for more pedestrian and widespread use in relational reasoning research.…”
Section: Research Gapsmentioning
confidence: 99%
“…For example, studies have shown that relational reasoning is evident in activities that entail both formal and informal learning (Galotti, 1989; Barwise, 1993) and manifests in such disciplines as medicine (Greenwood and King, 1995), engineering (Murphy et al, 2017), science and mathematics (Alexander, 2017;Resnick et al, 2017), reading (Kendeou et al, 2017), and writing (Egyed, 2010). There is a growing interest in relational reasoning, fueled in part by contemporary research in cognitive neuroscience (Baggetta and Alexander, 2016;Wertheim and Ragni, 2018;Gray and Holyoak, 2020) and in educational and cognitive psychology (e.g., Grossnickle et al, 2016;Jablansky et al, 2019). However, recognition of its importance goes back decades to work by James (1890), Spearman (1927), Cattell (1949), and others.…”
Section: Introductionmentioning
confidence: 99%
“…We do not attempt a meta-analysis, and our review does not aim to be exhaustive. Extending other recent reviews and meta-analyses (e.g., Wertheim & Ragni, 2018;Krawczyk, 2012Krawczyk, , 2017, we will consider behavioral and computational work that has informed neural investigations. We will focus on the central components of a network underlying relational integration and also consider other varieties of relational processing that are relatively independent of this system for relational integration.…”
Section: Introduction Relational Integration In Human Reasoningmentioning
confidence: 99%